Surgical treatment of the patient with Sturge-Weber syndrome - a case report - Adrian Gnatek; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
Vascular malformations associated with genetic syndromes lead to dysfunction of human body organs by blood supply impairment. Disorders in the structure of blood vessels walls result in developing pathological lesions called hemangiomas. The case describes a 16-year-old male patient with Sturge-Weber syndrome (SWS) who was treated surgically due to hemangioma of upper jaw. The patient suffered from typical for Sturge-Weber syndrome congenital disorders of other organs. In these cases surgical treatment requires deep analysis and proper procedure planning in the context of hemostasis.